Síntesis por radiación con microondas de nanotubos de carbono - Edgar González; Francisco González (Universitas Scientiarum)
Synthesis of carbon nanotubes by microwave radiation. Although at the present time a variety of methods and techniques is availablefor the synthesis and functionalization of carbon nanotubes, it is necessary to explore alternatives to improve the selective and homogeneousheating of the samples and to reduce the times to complete the processes. Microwave radiation offers an important opportunity to fulfil theserequirements, besides representing a method for the production of aligned carbon nanotubes in multi-layers that can be valuable forinvestigation, specifically in the biosensors design, purification systems, nanosystems of cathodic emission, catalytic electrodes for fuelcells, etc. We carried out a review of the use of microwave radiation for the production and functionalization of carbon nanotubes and reportthe synthesis of carbon nanotubes by microwaves with the use of silver nitrate as the catalyzer.